Sistem Pendukung Keputusan Pemilihan E-Commerce Menggunakan Pembobotan Entropy dan COPRAS - Citra, Puspa; Santoso, Heri Bambang; Sriyasa, I Wayan (PT. SNN MEDIA TECH PRESS, 2024)
The choice of e-commerce platform is crucial for businesses that want to expand their reach and increase sales online. By choosing the right e-commerce platform, businesses can optimize their online operations, increase customer satisfaction, and achieve sustainable growth in an increasingly competitive digital marketplace. This study aims to select e-commerce using a combination of entropy weighting methods and COPRAS in producing alternative assessments and ratings of existing e-commerce, so that it becomes a recommendation for the public in choosing an e-commerce as a transaction platform. The ranking results in the final e-commerce score are rank 1 obtained for Shoope e-commerce with a value of 100%, rank 2 obtained for Tokopedia e-commerce with a value of 95.93%, rank 3 obtained for Lazada e-commerce with a value of 80.93%, and rank 4 obtained for Blibli e-commerce with a value of 58.07%. The recommendation results for selecting an E-Commerce platform using a combination of Entropy and COPRAS weighting methods provide the highest recommendation to the Shoope E-Commerce platform with the highest value of 100%.